Credit routing for source-location privacy protection in wireless sensor networks - Lu, Zongqing (2013)
Source-location privacy became one of major issues due to the open nature of wireless sensor networks. The adversary can eavesdrop and trace the message movements so as to capture the source. In the paper, first we propose Credit routing to provide the source-location privacy protection. Credit routing is able to route the message within the assigned credit at each message and randomize the routing path. Unlike other location privacy protection schemes in WSN, Credit routing not only can provide strong protection but also precisely control the transmission cost of each message. Then, we propose Hybrid credit routing, which routes the message to the receiver through three phases: totally random walk, forwarding random walk and credit random walk. These phases provide tri-fold protection to prevent the source from being captured by the adversary. We evaluate our proposed schemes based on several metrics including safe period, latency and protection efficiency. The simulation results show that Credit is able to provide the strong and efficient protection compared with other schemes including Phantom, LPR and RRIN. It is also shown Hybrid improves the protection strength and efficiency even further. The performance of Credit and Hybrid can be tuned by the assigned credit. For real application, the credit can be the real power consumption for forwarding the message from the source to the sink. So both Credit and Hybrid can be used to precisely control the power consumption for source-location protection.